Pelaksanaan Kegiatan Mukhayyam al-Qur’an Intensif dalam Meningkatkan Motivasi Menghafal al-Qur’an Siswa SMA IT Darul Hikmah - Haliza Meida Firzannah; Nurhasnah Nurhasnah (Lembaga Yasin AlSys, 2026)
Intensive Mukhayyam Al-Qur’an activities have received attention in several studies, yet research that specifically discusses the implementation of this program in increasing students’ motivation to memorize the Qur’an in integrated Islamic school environments remains limited. This study aims to describe the implementation of intensive Mukhayyam Al-Qur’an activities and analyze their role in increasing students’ motivation to memorize the Qur’an at SMA IT Darul Hikmah. This study used a qualitative approach with a descriptive qualitative design, involving Grade X and XI students as well as tahfidz supervisors selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive analysis technique of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results show that Mukhayyam Al-Qur’an activities are implemented intensively and structurally through talaqqi, muroja’ah, tasmi’, motivational halaqah, qiyamul lail, and spiritual development. This program was able to increase students’ motivation to memorize the Qur’an, as reflected in their increased enthusiasm for memorization, discipline in muroja’ah, intensity of memorization submissions, and involvement in tahfidz activities. This finding contributes to the development of Islamic education studies, particularly regarding the relationship between a religious learning environment and motivation to memorize the Qur’an. The practical implications of this study indicate the importance of developing intensive tahfidz programs that are integrated with spiritual development and social support in Islamic school environments.